Estimating the Effect of Recurrent Infectious Diseases on Nutritional Status: Sampling Frequency, Sample-size, and Bias - Schmidt, Wolf-Peter; Genser, Bernd; Luby, Stephen P; Chalabi, Zaid (Journal of Health, Population and Nutrition, 2011)
There is an ongoing interest in studying the effect of common recurrent infections and conditions, such as diarrhoea, respiratory infections, and fever, on the nutritional status of children at risk of malnutrition. Epidemiological studies exploring this association need to measure infections with sufficient accuracy to minimize bias in the effect estimates. A versatile model of common recurrent infections was used for exploring how many repeated measurements of disease are required to maximize the power and logistical efficiency of studies investigating the effect of infectious diseases on malnutrition without compromising the validity of the estimates. Depending on the prevalence and distribution of disease within a population, 15-30 repeat measurements per child over one year should be sufficient to provide unbiased estimates of the association between infections and nutritional status. Less-frequent measurements lead to a bias in the effect size towards zero, especially if disease is rare. In contrast, recall error can lead to exaggerated effect sizes. Recall periods of three days or shorter may be preferable compared to longer recall periods. The results showed that accurate estimation of the association between recurrent infections and nutritional status required closer follow-up of study participants than studies using recurrent infections as an outcome measure. The findings of the study provide guidance for choosing an appropriate sampling strategy to explore this association. Key words: Diarrhoea; Epidemiology; Infections; Measurement; Nutritional status DOI: http://dx.doi.org/10.3329/jhpn.v29i4.8447 JHPN 2011; 29(4): 317-326